Inovação, comunicação e pequenos negócios em tempos de pandemia: relatos de experiência de agentes locais de inovação (Ali) (Comunicação & Inovação, 2021)
This paper presents the impacts of the pandemic on the innovative behavior of micro-enterprises and small businesses given the declarations of Innovation Local Agents. Within this context, the aim is to understand the issues faced by companies emphasizing communication as the main practice adopted to address the crisis.  For this purpose, through the application of in-depth interviews, exploratory descriptive research from the qualitative type was carried out. The results show that the use of digital communication was the main innovative factor in these companies and a viable way to confront the crisis.